Upaya Positivisasi Hukum Islam Wilayah Banjar (Telaah Eksistensi Harta Perpantangan Sebagai Ciri Khas Daerah) - Arif Fitria, Rizal; Sukarni, Sukarni; Hanafiah, M.; Muhajir, Ahmad (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This article discusses the efforts to positivize Islamic law in the Banjar region, with a particular focus on examining the existence of 'harta perpantangan' (inherited communal property) as a distinctive regional characteristic. 'Harta perpantangan' is a form of wealth management that has long been a tradition in the Banjar community. Although not explicitly regulated in Islamic law, this practice remains preserved and upheld by the community. This research employs a qualitative approach with a case study method. Data was collected through interviews, observation, and document study. The results show that the efforts to positivize Islamic law in the Banjar region have been carried out through several initiatives, such as the integration of customary law norms into regional regulations, the establishment of Islamic law-based institutions, and the development of sharia-compliant financial products. In the context of 'harta perpantangan', although it is not explicitly regulated in Islamic law, the Banjar community continues to maintain this practice with various adjustments and modifications to align it with sharia principles. This indicates an effort to accommodate local wisdom in the process of positivizing Islamic law in the Banjar region. Keywords: Positivization of Islamic Law, 'Harta Perpantangan', Banjar Community Abstrak Artikel ini mengkaji upaya positivisasi hukum Islam di wilayah Banjar dengan fokus khusus pada eksistensi harta perpantangan sebagai salah satu ciri khas daerah. Harta perpantangan merupakan konsep warisan budaya masyarakat Banjar yang memiliki nilai hukum dan sosial yang signifikan. Dalam konteks hukum Islam, positivisasi hukum bertujuan untuk mengintegrasikan norma-norma Islam ke dalam sistem hukum nasional secara formal. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus dan analisis dokumen untuk mengeksplorasi bagaimana harta perpantangan diakui dan diimplementasikan dalam hukum positif di wilayah Banjar. Temuan penelitian menunjukkan bahwa upaya positivisasi hukum Islam di Banjar tidak hanya memperkuat identitas budaya lokal, tetapi juga berkontribusi pada keberagaman hukum nasional Indonesia. Artikel ini mengusulkan beberapa rekomendasi untuk peningkatan harmonisasi antara hukum adat dan hukum Islam dalam kerangka hukum nasional, guna menjaga keberlanjutan tradisi dan memajukan keadilan sosial. Kata Kunci: Positivisasi, Hukum Islam, Adat Banjar, Eksistensi Harta Perpantangan.